Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can Some one tell me what this method is called and how it works With a detailed proof


I've been using this a lot in definite integration but haven't seemed to have realized why it is true. But whatever it is it always seems to work.

Basically a proof of how it is always true.

share|cite|improve this question
up vote 19 down vote accepted

Here is a pictorial argument.

$\displaystyle \int_a^b f(x) dx$ is the area under the curve $y=f(x)$ in the interval $(a,b)$ when you integrate from left to right. enter image description here $\displaystyle \int_a^b f(a+b-x) dx$ is the area under the curve $y=f(x)$ in the interval $(a,b)$ when you integrate from right to left. enter image description here Hence, both are equal.

share|cite|improve this answer
Or the graph of $g(x)=f(a+b-x)$ is obtained from the graph of $f(x)$ by reflection in the line $x=\frac{a+b}{2}$. – N. S. Jul 4 '12 at 16:06

Change of variables: $a+b-x=t$, $dx = -dt$, and $$ \int_a^b f(a+b-x)\, dx = -\int_b^a f(t)\, dt = \int_a^b f(t)\, dt. $$

share|cite|improve this answer
And why is the last one equal to $\int_a^b f(x)dx$? If $t=a+b-x$. – mavavilj Apr 19 at 10:28
@mavavilj Dummy variables... – Siminore Apr 19 at 12:00

it is just substitution, if we let $u = a+b-x$, we have $du = -dx$ and hence (note that $u = b$ when $x= a$ and vice versa) \begin{align*} \int_a^b f(x)\,dx &= \int_a^b f(u)\, du\\ &= \int_b^a f(a+b-x)\bigl(-dx\bigr)\\ &= -\int_b^a f(a+b-x)\,dx\\ &= \int_a^b f(a+b-x)\, dx \end{align*}

share|cite|improve this answer
But how is $\int_a^b f(x)dx = \int_a^b f(u)du$? – mavavilj Apr 19 at 10:48

Let the antiderivative of $f$ be $F$.

Then $-\int_a^b f(a+b-x) d(a+b-x) = -(F(a+b-b) - F(a+b-a)) = F(b) - F(a) = \int_a^bf(x)dx$ .

EDIT Thank you for the correction avatar

share|cite|improve this answer
How is $dx=-d(a+b-x)$? – mavavilj Apr 19 at 10:48

Define $u=a+b-x$ so that $dx=-du$. Then the boundary term $x=a$ gives $u=b$ and $x=b$ gives $u=a$. Changing variables in the integral gives:

$$\int_a^bf(x) \, dx = -\int_b^af(u) \, du = \int_a^bf(u) \, du=\int_a^bf(x) \, dx$$

Intuititively, instead of integrating from $a$ to $b$, you are starting at $u=a+b-a=b$ and integrating left to $a$, but then switching sign to account for the fact that you were integrating leftwards.

share|cite|improve this answer

Lets us define two functions $G1(x) = F(x)$ and $G2(x) = F(a+b-x)$

For any point $x$ in the range $x=a$ to $x=b$ we can define a variable scalar $P$ such that $x$ divides the interval $a...b$ in the ratio $(P)$:$(1-P)$ where $0 <= P <=1$.

Now we can define any point $x$ in two ways: $x1 = a + P(b-a)$ and $x2 = b - (1-P)(b-a)$

Now let us insert $x2$, $x1$ into the two different functions $G1$,$G2$

$G1(x) = F([x2]) = F([b - (1-P)(b-a)]) = F(a + P(b-a))$

$G2(x) = F(a+b-[x1]) = F(a + b - [a + P(b-a)]) = F(b - P(b-a))$

therefore $\int_0^1G1(x)\,\mathrm{d}P =\int_0^1G2(x)\,\mathrm{d}P$ because in the former integration we move across the interval from $x=a$ to $x=b$ and in the latter integration we move across the same interval from $x=b$ to $x=a$.

Therefore $\int_a^bF(x)$ = $\int_a^b F(a+b-x)$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.